The uses of medievalism in early modern England: recovery, temporality, and the “passionating” of the past - Jones, Mike Rodman (Taylor & Francis, 2018)
The premodern past was desired and deployed in a myriad of different ways in sixteenth-century England. The period of the English Reformations produced a generative, complex, and paradoxical range of feelings for the premodern. Many sixteenth-century texts were multiply medievalist, making use of literary figures, generic forms, and cultural phenomena in unexpected ways. Various senses of temporality—understandings of the shapes and nature of cultural time—were often foregrounded. Reformation historiography was often sectarian and combative, but also sought tangible contact with the textual remains of the past. These feelings for the premodern were then unavoidably present in the 1590s, but were subject to use in nascent literary forms that were self-consciously avant-garde in different ways. Antiquity and archaism were brought together with a heightened sense of contemporaneity. In prose fiction, the premodern could be used in different forms of scandalously risqué, comic, and autobiographical narratives. In historical poetry produced in the same decade, a new literary mode made poetic capital out of a heightened emotional discourse associated with premodern history and culture.